2004
DOI: 10.1016/j.jacc.2004.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Wall stress modulates brain natriuretic peptide production in pressure overload cardiomyopathy

Abstract: In patients with AS, BNP appears to be regulated not only by systolic but also by diastolic load. This supports the hypothesis that myocardial stretch modulates BNP production in human pressure overload hypertrophy/failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
125
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(142 citation statements)
references
References 40 publications
11
125
0
6
Order By: Relevance
“…For example, BNP expression undergoes compensatory upregulation under stressed conditions of the heart, including heart failure and cardiac hypertrophy. 25,26 BNP transgenic mice exhibit attenuated albuminuria and renal damage after subtotal nephrectomy, 27 and the overexpression of BNP in mice also improves immune-mediated renal injury. 28 Adrenomedullin is abundantly expressed in heart tissue and upregulated by cardiac stress, including pressure overload and myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…For example, BNP expression undergoes compensatory upregulation under stressed conditions of the heart, including heart failure and cardiac hypertrophy. 25,26 BNP transgenic mice exhibit attenuated albuminuria and renal damage after subtotal nephrectomy, 27 and the overexpression of BNP in mice also improves immune-mediated renal injury. 28 Adrenomedullin is abundantly expressed in heart tissue and upregulated by cardiac stress, including pressure overload and myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,16 It has been suggested that LV end-diastolic wall stress is the most important hemodynamic parameter regulating the levels of circulating BNP. 12,17 Of note, circulating BNP reflects the balance between BNP release and elimination. In contrast, our data suggest that LVESWS is the key loading parameter for ⌬ A-CS BNP, that is, cardiac BNP release, indicating that LV geometry and afterload rather than filling pressures are the most important mechanical determinants of cardiac BNP release.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our data suggest that LVESWS is the key loading parameter for ⌬ A-CS BNP, that is, cardiac BNP release, indicating that LV geometry and afterload rather than filling pressures are the most important mechanical determinants of cardiac BNP release. The strength of our study compared with previous ones evaluating the relationship between plasma BNP levels and wall stress 12,17 lies in the fact that we studied subjects with a broad range of LV dysfunction, including a group with normal LVEF and normal LV diastolic function. Most importantly, in our study we measured ⌬ A-CS BNP rather than peripheral BNP.…”
Section: Discussionmentioning
confidence: 99%
“…However, at a later stage, when this compensatory mechanism is overridden, LV wall stress and filling pressure increase triggering BNP activation and release. 19 In symptomatic AS, BNP release has been shown to reflect the elevation in LV filling pressures. 20 In symptomatic or asymptomatic severe AS with structural impairment such as diastolic dysfunction, LA dilatation, LV hypertrophy, and fibrosis, elevated single BNP level measurement is a marker of already elevated LV filling pressures predicting poor short-term outcome.…”
Section: Pathophysiology Of Bnp Release In Asmentioning
confidence: 99%